2000
DOI: 10.1364/ao.39.004284
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap mesosphere wind observations: comparisons of simultaneous measurements with a Fabry–Perot interferometer and a field-widened Michelson interferometer

Abstract: Polar cap mesospheric winds observed with a Fabry-Perot interferometer with a circle-to-line interferometer optical (FPI/CLIO) system have been compared with measurements from a field-widened Michelson interferometer optimized for E-region winds (ERWIN). Both instruments observed the Meinel OH emission emanating from the mesopause region (approximately 86 km) at Resolute Bay, Canada (74.9 degrees N, 94.9 degrees W). This is the first time, to our knowledge, that winds measured simultaneously from a ground-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Accuracy of measurements is typically 1 m/s for a single observation, with an integration time of 1-2 s. A full set of measurements-zonal and meridional winds -takes about 20 min in the instrument configuration used for this paper. An excellent correlation was found in simultaneously measured wind velocities (corresponding to the ∼97 km green-line airglow emission) from ERWIN and a ground-based Fabry-Perot instrument (CLIO), also located at Resolute Bay (Fisher et al, 2000). Uninterrupted measurements are possible during darkness (polar winter) without significant cloud cover or bright moonlight within the instrument field-of-view.…”
Section: Datamentioning
confidence: 77%
“…Accuracy of measurements is typically 1 m/s for a single observation, with an integration time of 1-2 s. A full set of measurements-zonal and meridional winds -takes about 20 min in the instrument configuration used for this paper. An excellent correlation was found in simultaneously measured wind velocities (corresponding to the ∼97 km green-line airglow emission) from ERWIN and a ground-based Fabry-Perot instrument (CLIO), also located at Resolute Bay (Fisher et al, 2000). Uninterrupted measurements are possible during darkness (polar winter) without significant cloud cover or bright moonlight within the instrument field-of-view.…”
Section: Datamentioning
confidence: 77%
“…The zero wind is determined from the average of the four cardinal directions. Comparisons of simultaneous measurements with a Fabry‐Perot interferometer (also stationed at Resolute Bay) and ERWIN have been done [ Fisher et al , 2000] and the two instruments are in excellent agreement.…”
Section: Resolute Bay Wind Measurementsmentioning
confidence: 99%
“… Fisher et al [1999] presented the first FPI/CLIO mesopause wind results above Resolute. Fisher et al [2000] showed that both optical techniques provide equivalent observations of the mesopause winds at Resolute.…”
Section: Instrumentationmentioning
confidence: 99%
“…Observations at the northern polar latitudes are sparse due to the lack of ground‐based instruments at suitable sites and appropriately‐instrumented satellites with high orbital inclination. There exist only a few works that address the dynamics of the neutral MLT in the northern polar region—research has focused on observations at Resolute (74.9°N, 94.9°W) [ Fisher et al , 1999, 2000] and Eureka (80°N, 85°W) [ Sivjee et al , 1994; Oznovich et al , 1995; Walterscheid and Sivjee , 1996; Oznovich et al , 1997].…”
Section: Introductionmentioning
confidence: 99%